First-line liposomal irinotecan with oxaliplatin, 5-fluorouracil and leucovorin (NALIRIFOX) in pancreatic ductal adenocarcinoma: A phase I/II study. (July 2021) - Wainberg, Zev A.; Bekaii-Saab, Tanios; Boland, Patrick M.; Dayyani, Farshid; Macarulla, Teresa; Mody, Kabir; Belanger, Bruce; Maxwell, Fiona; Moore, Yan; Thiagalingam, Arunthathi; Wang, Tiffany; Zhang, Bin; et al.
Abstract: Background: This open-label, phase I/II study evaluated safety and efficacy for first-line liposomal irinotecan + oxaliplatin + 5-fluorouracil + leucovorin (NALIRIFOX). Methods: Patients (aged ≥18 years) had locally advanced/metastatic pancreatic ductal adenocarcinoma (mPDAC), with an Eastern Cooperative Oncology Group performance status score of 0/1 and adequate organ function. Primary objectives were to determine the maximum tolerated dose (MTD) and to evaluate safety and tolerability. Treatment-emergent adverse events (TEAEs) were graded using National Cancer Institute Common Terminology Criteria for Adverse Events v4.03. Efficacy end-points included progression-free survival (PFS) and overall survival (OS); disease assessments used Response Evaluation Criteria in Solid Tumors 1.1. Results: The MTD (liposomal irinotecan 50 mg/m 2 [free-base equivalent], oxaliplatin 60 mg/m 2, 5-fluorouracil 2400 mg/m 2, leucovorin 400 mg/m 2 every 2 weeks) was based on dose-limiting toxicities and cumulative safety data in four dose-exploration cohorts. The MTD was received by 32 of 56 patients, seven during dose exploration and 25 during dose expansion (median age 58.0 years [range, 39–76], 28 [87.5%] with metastatic disease at diagnosis [29 at study entry], and one receiving study treatment at data cutoff [26 February 2020]). Of these patients, 22 of 32 had grade ≥3 treatment-related TEAEs, most commonly neutropenia (31.3%), febrile neutropenia (12.5%) and hypokalaemia (12.5%); ten had serious treatment-related TEAEs; and three died from TEAEs considered unrelated to treatment. Median PFS and OS were 9.2 (95% CI: 7.69–11.96) and 12.6 (8.74–18.69) months, respectively. Conclusion: First-line NALIRIFOX for patients with locally advanced/mPDAC was generally manageable and tolerable. A randomised, controlled phase III study is underway. Graphical abstract: Image 1 Highlights: Patients with mPDAC received 1L NALIRIFOX every 2 weeks in this phase I/II trial. MTD: liposomal irinotecan 50 mg/m 2, OX 60 mg/m 2, 5-FU 2400 mg/m 2, LV 400 mg/m 2 . No unexpected safety outcomes were apparent in the 32 patients receiving the MTD. Median PFS was 9.2 months (95% CI: 7.69–11.96) and OS was 12.6 months (8.74–18.69). Based on these findings, a phase 3 study of 1L NALIRIFOX vs gem/nab has started.